Writing and editing for digital media - Carroll, Brian, 1965- (Routledge, 2014)
"Writing and Editing for Digital Media, 2nd edition, teaches students how to write effectively for digital spaces -- whether crafting a story for a website, blogging or using Twitter to cover a breaking news story or event. The lessons and exercises in each chapter help students build a solid understanding of the ways that digital communications have introduced opportunities for dynamic storytelling and multi-directional communication. Writing and Editing for Digital Media also addresses the graphical, multimedia, hypertextual and interactive elements that come into play when writing for digital platforms and designing digital spaces. The book teaches students not only to create content, but also to become careful, creative managers of that content. Based on Brian Carroll's extensive experience teaching the course, this revised and updated edition pays particular attention to opportunities presented by the growth of social media and mobile media. Chapters aim to: Assist digital communicators in understanding the social networked, increasingly mobile, always-on, geomapped, personalized media ecosystem; Help writers across multiple communication fields (journalism, marketing, PR, technical writing) make the transition from print to digital; Teach communicators to approach storytelling from a multimedia, multi-modal, interactive perspective. A companion website with exercises and assignments gives students the tools they need to put theory into practice"--